2014
DOI: 10.1016/j.nmd.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regions of the DMD 3′ UTR regulate translation and mRNA abundance in cultured myotubes

Abstract: Duchenne muscular dystrophy (DMD), a severe muscle-wasting disease, is caused by mutations in the DMD gene, which encodes for the protein dystrophin. Its regulation is of therapeutic interest as even small changes in expression of functional dystrophin can significantly impact the severity of DMD. While tissue-specific distribution and transcriptional regulation of several DMD mRNA isoforms has been well characterized, the post-transcriptional regulation of dystrophin synthesis is not well understood. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
1
2
1
Order By: Relevance
“…Instead, the coding sequence is preceded by a standard chimaeric intron. While previous studies showed a role for 5′ and 3′ UTR regions into controlling tissue-specific expression and transcriptional regulation of Dystrophin (see Larsen and Howard, 2014 and references therein), our results show that UTR regions are dispensable for accumulation of the mRNA at the tip. It is therefore unlikely that Dystrophin RNA accumulation at the tips is due to specific RNA transport since that would most likely require the presence of the untranslated regions (for review see Kloc et al, 2002 ; Holt and Bullock, 2009 ).…”
Section: Discussioncontrasting
confidence: 79%
“…Instead, the coding sequence is preceded by a standard chimaeric intron. While previous studies showed a role for 5′ and 3′ UTR regions into controlling tissue-specific expression and transcriptional regulation of Dystrophin (see Larsen and Howard, 2014 and references therein), our results show that UTR regions are dispensable for accumulation of the mRNA at the tip. It is therefore unlikely that Dystrophin RNA accumulation at the tips is due to specific RNA transport since that would most likely require the presence of the untranslated regions (for review see Kloc et al, 2002 ; Holt and Bullock, 2009 ).…”
Section: Discussioncontrasting
confidence: 79%
“…They may reflect the involvement of 5′UTR in mechanisms governing transcriptional regulation. Indeed, the longer 5′UTRs of SEGs may reflect lower translation rates compared with MEGs, in agreement with previous findings that mRNAs with high translation rates often contain short 5′UTRs (Larsen & Michael, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Despite our observations, one has to keep in mind that SNPs may not be the only cause of differences in BCO2 gene expression between the Qingjiao Ma and Guangxi Huang chicken breeds. There may be other factors that can be responsible for the reduced expression of the BCO2 gene expression in the Guangxi Huang chicken breed, such as DNA methylation [ 40 , 41 , 42 ], histone modification [ 43 , 44 , 45 ], and UTR function and, thus, translational modification [ 46 ]. Additional experiments need to be performed to elucidate the specific difference in BCO2 expression in the skin of Qingjiao Ma and Guangxi Huang chicken breeds without differences in gene expression in any other tissue.…”
Section: Discussionmentioning
confidence: 99%